Transfer dynamics of macroplastics in estuaries – New insights from the Seine estuary: Part 2. Short-term dynamics based on GPS-trackers. (November 2020) - Tramoy, R.; Gasperi, J.; Colasse, L.; Silvestre, M.; Dubois, P.; Noûs, C.; Tassin, B.
Abstract: The dynamics of plastic debris were assessed in the Seine River, especially in the estuary, using plastic bottles equipped with GPS-trackers. In one year, 50 trajectories were recorded, covering a wide range of hydrometeorological conditions. Results show a succession of stranding/remobilization episodes in combination with alternating upstream and downstream transport in the estuary. In the end, 100% of the tracked bottles stranded somewhere, for hours or weeks, from one to several times at different sites. The overall picture shows that different physical phenomena interact with various time scales ranging from hours/days (high/low tides) to weeks/months (spring/neap tides and highest tides) and years (seasonal river flow). Thus, the fate of plastic debris is highly unpredictable, but the consequence of those interactions is that the transfer of debris is chaotic and not straightforward, and its residence time is much longer than the transit time of water. Highlights: GPS-trackers in bottles were used to monitor plastic transport in the Seine River. The 50 trajectories recorded showed stranding/remobilization episodes. Remobilization processes and bi-directional transport were favored by tides. Total distance travelled was 6 times greater in the estuary than upriver. Only flood events may flush plastic debris out of the estuary.